2018
DOI: 10.3390/toxins10040154
|View full text |Cite
|
Sign up to set email alerts
|

Bavachinin Induces Oxidative Damage in HepaRG Cells through p38/JNK MAPK Pathways

Abstract: Drug-induced liver injury is one of the main causes of drug non-approval and drug withdrawal by the Food and Drug Administration (FDA). Bavachinin (BVC) is a natural product derived from the fruit of the traditional Chinese herb Fructus Psoraleae (FP). There have been reports of acute liver injury following the administration of FP and its related proprietary medicines. To explore BVC hepatotoxicity and its mechanisms, we used the HepaRG cell line. In our recent research, we showed that BVC induces HepaRG cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Data from qRT-PCR and Western blot showed that sevoflurane could suppress the PCNA, Twist, MMP-2 and MMP-9 expression and enhanced the cleaved-caspase-3/caspase-3 MAPK is an important pathway of intracellular signal transduction, an intersection point and common pathway of multiple signal transduction, which is widely distributed in the cytoplasm and transmits extracellular stimulus signals to the nucleus, and it can regulate of cell proliferation, differentiation and stress. 33 P38 and JNK were reported to have belonged to principal MAPK pathways, 34,35 and the expressions of p38 and JNK were assessed in our study. Dramatically decreases of p-p38/p38 and p-JNK/JNK expressions were observed in OC cells of sevoflurane groups compared to that of the control group.…”
Section: Discussionmentioning
confidence: 93%
“…Data from qRT-PCR and Western blot showed that sevoflurane could suppress the PCNA, Twist, MMP-2 and MMP-9 expression and enhanced the cleaved-caspase-3/caspase-3 MAPK is an important pathway of intracellular signal transduction, an intersection point and common pathway of multiple signal transduction, which is widely distributed in the cytoplasm and transmits extracellular stimulus signals to the nucleus, and it can regulate of cell proliferation, differentiation and stress. 33 P38 and JNK were reported to have belonged to principal MAPK pathways, 34,35 and the expressions of p38 and JNK were assessed in our study. Dramatically decreases of p-p38/p38 and p-JNK/JNK expressions were observed in OC cells of sevoflurane groups compared to that of the control group.…”
Section: Discussionmentioning
confidence: 93%
“…The results showed that prepromoting autophagy can delay the senescence of MSCs and decrease ROS production before the induction of MSC senescence. A close relationship exists between ROS and MAPKs, especially c‐Jun N‐terminal kinases (JNK) and p38 . Additionally, the JNK/p38 pathway plays an important regulatory role in cellular senescence .…”
Section: Introductionmentioning
confidence: 99%
“…For focal brain ischemia, the mouse middle cerebral artery occlusion and reperfusion model (MCAO/R) was used as described previously [ 37 , 38 , 39 , 40 ]. In brief, animals were anaesthetized with 50 mg·kg −1 Zoletil 50 via intramuscular injection (Virbac S.A, Carros, France) and maintained at a half-dose.…”
Section: Methodsmentioning
confidence: 99%